Trials and Progress Prediction of Covid-19 Vaccine Using Linear Regression and SIR Parameters - Ananda Aulia Rizky; Novi Rahmawati; Adil El-Faruqi; Faisal Dharma Adhinata; Nur Ghaniaviyanto Ramadhan (School of Computing, Telkom University, 2021)
This study aims to elucidate the worldwide effectiveness of the COVID-19 vaccine to reduce the number of COVID-19 patients. Currently, almost all countries in the world are trying to overcome COVID-19 by imposing a lockdown system. The government is also looking for a solution to suppress the spread of COVID-19 by administering a vaccine. Vaccination is one of the efforts that are considered effective in overcoming COVID-19 in affected countries. At least 85 types of vaccines are still in the development stage, while the vaccines that have been agreed upon are Pfizer-Biotech messenger RNA vaccines (bnt162b2) and Moderna (mRNA-1273). The hope is that the COVID-19 outbreak can be handled immediately to restore the residents' economy with vaccination. The methodology used in this study uses data mining with linear regression and SIR techniques to evaluate whether circulating vaccines can effectively suppress the spread of COVID-19.